Comparison of Dye Spread Pattern and Nerve Involvement between Suprainguinal and Infrainguinal Fascia Iliaca Blocks with Different Injectate Volumes: A Cadaveric Evaluation - Tae-Hyeon Cho; Byongnam Jun; Hun-Mu Yang; Shin Hyung Kim (Medicina)
Background and Objectives: Fascia iliaca compartment block (FICB) is an effective and relatively safe technique in perioperative pain management for hip surgery. However, blockade of the obturator nerve (ON) using this technique remains controversial. This study aimed to compare dye spread patterns and nerve involvement in the suprainguinal FICB (S-FICB) and infrainguinal FICB (I-FICB) approaches using different volumes of dye. Materials and Methods: Following randomization, 6 S-FICBs and 6 I-FICBs were performed on the left or right sides of 6 unembalmed cadavers. For each block, 30 mL or 60 mL of dye solution was injected. The extent of dye spreading and the staining pattern in the lumbar plexus branches were investigated using anatomical dissection. Results: Twelve injections were successfully completed. The lateral femoral cutaneous nerve (LFCN) and femoral nerve (FN) were consistently stained in all injections. Extended dye spread toward lumbar plexus branches was observed volume-dependently in S-FICBs. However, I-FICBs with an increased volume only showed dye spreading in the caudad direction limited to within the fascia iliaca. When 30 mL of dye was used, the ON was not stained with either approach. A stained ON was only observed in S-FICBs when 60 mL of dye was used. Conclusions: In this cadaveric evaluation, the ON was not stained in either FICB approach with the volume of injectate commonly used in clinical practice. The S-FICBs but not I-FICBs using a high volume of injectate resulted in extended spreading to the lumbar plexus branches.